ANALISIS GAYA BAHASA EMOTIF “FAJAR SADBOY” DALAM PODCAST YOUTUBE PODKESMAS: KAJIAN STILISTIKA - Fahrani Almira Rizkya Haryanto; Eko Suroso (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of information technology in the digital era has changed people's communication patterns, making podcasts an interaction space that allows spontaneous and natural expression of language. This study aims to analyze the form, function, and meaning of the emotive language style used by Fajar Sadboy in the YouTube podcast uploaded by Podkesmas and understand its role in representing the emotional state of the speaker and building interaction with the audience. This study uses a descriptive qualitative approach with a stylistic analysis framework and the function of the Jakobson Roman language. Data was collected from the video podcast